Barriers to Girls’ Education in Rural India: An Examination of the Link Between Poverty, Patriarchy, And Access to Quality Education in Tamil Nadu - Meenakshi, Sridevi M; Karthikeyan, B (Sakha: Multidisciplinary Journal of Science, Art & Technology, 2025)
Education is the protuberant tool for ameliorate the status of marginalized or weaker session in India. Indeed, the progress gradually made by self determination and the aid of the Government. However, it has some barriers to getting proper education the rural areas, especially the women. Despite India’s progress in expanding options in education, girls from rural areas have still found some serious impediments to obtaining a good education. The complicated interplay of poverty, deep-seated patriarchal attitudes, and a lack of proper educational infrastructure in general puts limitations on rural girls in terms of achieving education and developing their socioeconomic potential. The paper, therefore, tries to understand the complex interrelation among these factors by highlighting subtle impediments to girls’ schooling in rural India and pointing out solutions for development.